2023
DOI: 10.1021/acs.est.3c00327
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticulate Silica Internalization and Its Effect on the Growth and Yield of Groundnut (Arachis hypogaea L.)

Abstract: In recent years, foliar applications of nanoparticles are increasingly being employed in agricultural fields as fertilizers to enhance crop yields. However, limited studies are available on the foliar uptake of nanoscale nutrients and their interaction with plants. In this study, we reported the effects of foliar spray with varied concentrations of nanoscale silica (N-SiO2) and bulk tetraethyl orthosilicate (TEOS at 2000 ppm) on the growth and yield of groundnut. Nanosilica was prepared by a sol–gel method and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
(98 reference statements)
0
5
0
Order By: Relevance
“…4,5 Therefore, it was reported that monosilicic acid, orthosilicic acid, and inorganic complex forms are the main forms of Si fertilizer at present and are being widely employed in rice cultivation. 6 Unfortunately, monosilicic acid and orthosilicic acid with higher solubility and absorption rates may induce potential phytotoxicity in plants. The disadvantage can be remedied through the use of nanotechnology in which nanoscale silicon has completely different particle size and surface area compared to natural silicon, thereby affecting its uptake and translocation in rice plants.…”
Section: ■ Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…4,5 Therefore, it was reported that monosilicic acid, orthosilicic acid, and inorganic complex forms are the main forms of Si fertilizer at present and are being widely employed in rice cultivation. 6 Unfortunately, monosilicic acid and orthosilicic acid with higher solubility and absorption rates may induce potential phytotoxicity in plants. The disadvantage can be remedied through the use of nanotechnology in which nanoscale silicon has completely different particle size and surface area compared to natural silicon, thereby affecting its uptake and translocation in rice plants.…”
Section: ■ Introductionmentioning
confidence: 99%
“…9 Similarly, Prasad et al found that the foliar application of SiNPs could increase the growth and yield of groundnut. 6 Our previous studies indicated that the pretreatment of SiNPs could alleviate cadmium (Cd) toxicity in rice suspension cells in a sizedependent manner by regulating the expression of Cd-and Sirelated genes. 10 Additionally, the addition of SiNPs could inhibit the uptake of arsenic (As) in rice cells by improving the mechanical force of cell walls and regulating As-related genes under As stress.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such a strategy may be the “nano agriculture”, which has been recently developed. ,, Nanoparticles (NPs) have a minimum one-dimensional size of 100 nm and unique properties compared to their bulk counterparts . Using NPs as a development strategy for sustainable agriculture has emerged as a new research direction.…”
Section: Introductionmentioning
confidence: 99%